DESAIN PADEYE UNTUK PROSES PENGANGKATAN STRUKTUR PROCESS DECK (PD-1) PADA PROYEK JANGKRIK FLOATING PRODUCTION UNIT (FPU) DI PERUSAHAAN PT. SAIPEM KARIMUN YARD - Sutrisno, Tri; Susilo, Trisno; Hilmy, Zakwan; Tyas Adi, Fajar; Dasira, Alyuan; Zaki Prawira, Muhammad; Pradana Putra, Andrew (JURNAL JALASENA, 2024)
Padeye is an object shaped semicircle that made of metal and welded to a profile. The top priority in lifting process is the safety of the structure to be lifted. The structure must not suffer damage or overstress during the lifting process. This causes in mendesai padeye must bethrough careful calculation so that the resulting design is in accordance with the load to be lifted that will be lifted. This research uses a quantitative method by using design calculations and loading on the padeye design. The results research shows that the padeye design for a 100-ton load plan with dimensions Length 360mm, Width 260 and Height 400mm has a stress below the allowable stress so it is safe to use so it is safe to use.